Depiction of Lord Indra - Temples of India Project Team (Jio Institute, 2024)
The adhisthana has depictions of various Hindu gods and goddesses framed within elaborately carved panels. This panel may be a depiction of Lord Indra who is king of the devas (celestial beings) and ruler of swarga (heavenly realm). Indra is also the dikpala (guardian of directions) of the east, hence he is placed facing the east direction. The central figure is a crowned male standing in samapada mudra (feet equally balanced) and carrying a vajra (thunderbolt). An elephant is standing behind (its head visible on the left) which could be the white elephant Airavata, the mount of Lord Indra. Based on the vajra and the elephant, the figure could be identified with Lord Indra, who is king of the devas and ruler of swarga.